Strategi Penerapan Lima Nilai Budaya Kerja di Kementerian Agama Menuju Pelayan Prima - Ahmad Zainuri (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2016)
Work culture is a philosophy as values into the nature, customs, and Work culture was a philosophy as values that became the nature, habits, and the driving force that was owned by every individual in the working environment of an organization. If it was associated with the organization, especially in the Ministry of Religion, the work culture showed how the values of work culture internalized by certain means (vehicle), so that people could feel the excellent service from government organizations of Religion Ministry.